Pharmacological characterization of JWX-A0108 as a novel type I positive allosteric modulator of α7 nAChR that can reverse acoustic gating deficits in a mouse prepulse inhibition model - Sun Li-lan; Yang Tao-yi; Wei Ning-ning; Lu Wei; Jiao Wen-xuan; Zhou Qi-qi; Miao Yong-zhen; Gao Qin; Wang Xin-tong; Sun Qi; Wang KeWei (Acta Pharmacologica Sinica, 2019)
The α7 nicotinic acetylcholine receptor (α7 nAChR) is a ligand-gated Ca2+-permeable homopentameric ion channel implicated in cognition and neuropsychiatric disorders. Pharmacological enhancement of α7 nAChR function has been suggested for improvement of cognitive deﬁcits. In the present study, we characterized a thiazolyl heterocyclic derivative, 6-(2-chloro-6-methylphenyl)-2-((3-ﬂuoro-4-methylphenyl)amino)thiazolo[4,5-d]pyrimidin-7(6H)-one (JWX-A0108), as a novel type I α7 nAChR positive allosteric modulator (PAM), and evaluated its ability to reverse auditory gating and spatial working memory deﬁcits in mice. In Xenopus oocytes expressing human nAChR channels, application of JWX-A0108 selectively enhanced α7 nAChR-mediated inward current in the presence of the agonist ACh (EC50 value = 4.35 ± 0.12 µM). In hippocampal slices, co-application of ACh and JWX-A0108 (10 µM for each) markedly increased both the frequency and amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs) recorded in pyramidal neurons, but JWX-A0108 did not affect GABA-induced current in oocytes expressing human GABAA receptor α1β3γ2 and α5β3γ2 subtypes. In mice with MK-801-induced deﬁcits in auditory gating, administration of JWX-A0108 (1, 3, and 10 mg/kg, i.p.) dose-dependently attenuates MK-801-induced auditory gating deﬁcits in ﬁve prepulse intensities (72, 76, 80, 84, and 88 dB). Furthermore, administration of JWX-A0108 (0.03, 0.1, or 0.3 mg/kg, i.p.) signiﬁcantly reversed MK-801-induced impaired spatial working memory in mice. Our results demonstrate that JWX-A0108 is a novel type I PAM of α7 nAChR, which may be beneﬁcial for improvement of cognitive deﬁcits commonly found in neuropsychiatric disorders such as schizophrenia and Alzheimer’s disease.